Root-knot nematode in garlic caused by Meloidogyne species: first record from Karnal district of Haryana state - S Pandey, R C Gupta, (Journal of Spices and Aromatic Crops, 2019)
Garlic (Allium sativum L.) is an important spice crop cultivated all over the country during Rabi season except in Ooty hills of Tamil Nadu where it is grown during rainy season. Garlic suffers from various fungal, bacterial as well as viral diseases causing severe yield loss in different cultivated areas in the country. During a survey in garlic fields at village Muradgarh, Tahsil-Indri of Karnal district of Haryana in November, 2016, a number of small, medium and big root galls mostly formed in root tips were observed in six week old garlic plants on local cultivar-Sankar. The infestation of root-knot nematode in garlic was severe and noticed in patches in the field. To the best of our knowledge, this is the first report of root-knot nematode affecting garlic from Karnal district of Haryana.